ISLAM, SCIENCE AND LOCAL CULTURE: OPPORTUNITIES AND CHALLENGE IN THE ERA OF SOCIAL MEDIA - Baharuddin, Baharuddin (The Pontianak State Institute of Islamic Studies, 2024)
Moeslem believe that life order in Islam is the most perfect religion. In Islamic teaching and also in Al-Qur’an as the main reseourch of Islam, clearly stated about that. The fact obout that significant Islamic teachings also shown in local and global daily life of Moeslem. Science and local culture become a unity that build in a good term of communication and interaction, especially in certain groups and region. Based on that previouse statement, nowdays, there are a lot of opportunities and challenges than appear in the era of social media. Local culture happen and become pioneer ini terms of social media development to support daily living. But, as the opportunities also come along with the challenges that we have to pay particular attention. Based on thet case this study become necessary. As moeslems, we have to remember that local culture ini social life based on Islamic teachings. This issues finally become the main study in this article because the basic of local culture in society should be taken from Islamic values, how far social media usage affected local culture. As we know, social media give us a lot of advantages along with the disadvantages. We should seek for the best way in order to minimize the disadvantages.